¿Hay que sancionar la piratería?: la protección de la propiedad intelectual - Matos, Nancy (2004)
This work presents a set of reflections on the protection of intellectual property from the perspective of consumer behaviour. It emphasizes that piracy is a complex issue because of the difficulty of establishing benefits and damages and because it causes ethical dilemmas between copyright and the rights of others. After focusing the issue and pointing out the magnitude of the piracy of books, software, discs and films, it analyses what the segmentation strategies of the companies mean, as well as the fact that, thanks to piracy, consumers with fewer resources they can access markets from which, in other circumstances, they would be excluded.